Turbulent vertical heat flux under Antarctic on-shelf sea ice intensified by the Amundsen Sea Undercurrent - Xingchi Wang; Alessandro Silvano; Yvonne Firing; Bieito Fernández Castro; Carl P. Spingys; Tiago S. Dotto; Louis Clément; Paul R. Holland; Alberto C. Naveira Garabato (Communications Earth & Environment)
Abstract The Amundsen Sea Undercurrent, off West Antarctica, transports warm Circumpolar Deep Water onto the continental shelf, driving basal melting when it reaches the ice shelves through troughs. However, vertical heat loss from the warm inflow to the cold upper ocean remains understudied. Here we use observations and numerical modeling to investigate mixing-induced vertical heat flux in a major trough, finding: (1) turbulent mixing transfers 1.7 W m−2 of heat to the upper ocean during observational period, potentially reducing sea ice growth by 0.2 m yr−1; and (2) mixing is modulated by undercurrent strength, with stronger undercurrent enhancing vertical shear across the on-shelf thermocline, promoting internal wave breaking and mixing. This flux is non-negligible in the on-shelf heat budget, particularly on annual and longer timescales. Our findings highlight the occurrence of vertical heat exchange over the Amundsen Sea shelf and indicate its potential role in modulating sea ice and ice-shelf melting.